A cyclophilin homology domain-independent role for Nup358 in HIV-1 infection. - Anne M Meehan; Dyana T Saenz; Rebekah Guevera; James H Morrison; Mary Peretz; Hind J Fadel; Masakazu Hamada; Jan van Deursen; Eric M Poeschla (PLoS Pathogens, 2014)
The large nucleoporin Nup358/RanBP2 forms eight filaments that project from the nuclear pore into the cytoplasm where they function as docking platforms for nucleocytoplasmic transport receptors. RNAi screens have implicated Nup358 in the HIV-1 life cycle. The 164 C-terminal amino acids of this 3,224 amino acid protein are a cyclophilin homology domain (Nup358Cyp), which has potential to bind the HIV-1 capsid and regulate viral progress to integration. Here we examined the virological role of Nup358 in conditional knockout mouse cells and in RNAi-depleted human CD4⁺ T cells. Cre-mediated gene knockout was toxic and diminished HIV-1 infectivity. However, cellular health and HIV-1 susceptibility were coordinately preserved if, prior to gene inactivation, a transposon was used to express all of Nup358 or only the N-terminal 1340 amino acids that contain three FG repeats and a Ran-binding domain. HIV-1, but not N74D capsid-mutant HIV-1, was markedly sensitive to TNPO3 depletion, but they infected 1-1340 segment-complemented Nup358 knockout cells equivalently. Human and mouse CypA both rescued HIV-1 in CypA gene⁻/⁻ Jurkat cells and TRIM-Nup358Cyp fusions derived from each species were equally antiviral; each also inhibited both WT and N74D virus. In the human CD4⁺T cell line SupT1, abrupt Nup358 depletion reduced viral replication but stable Nup358-depleted cells replicated HIV-1 normally. Thus, human CD4⁺ T cells can accommodate to loss of Nup358 and preserve HIV-1 susceptibility. Experiments with cylosporine, viruses with capsids that do not bind cyclophilins, and growth arrest did not uncover viral dependency on the C-terminal domains of Nup358. Our data reinforce the virological importance of TNPO3 and show that Nup358 supports nuclear transport functions important for cellular homeostasis and for HIV-1 nuclear import. However, the results do not suggest direct roles for the Nup358 cyclophilin or SUMO E3 ligase domains in engaging the HIV-1 capsid prior to nuclear translocation.